2023
DOI: 10.1101/2023.02.10.527944
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving cell-free expression of membrane proteins by tuning ribosome co-translational membrane association and nascent chain aggregation

Abstract: Cell-free gene expression (CFE) systems are powerful tools for transcribing and translating genes outside of a living cell. Given their diverse roles in nature, synthesis of membrane proteins is of particular interest, but their yield in CFE is substantially lower than for soluble protein. In this paper, we study factors that affect the cell-free synthesis of membrane proteins and develop a quantitative kinetic model of their production. We identify that stalling of membrane protein translation on the ribosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…These results correspond to the previous time series ( Figure 2 b) and additionally suggest the requirement of further protein processing time for higher order oligomer assembly. It should be noted that the absence of microsomes reduced the protein yield, consistent with other studies [ 23 ] and thus causes overall weaker protein bands in the autoradiogram.…”
Section: Resultssupporting
confidence: 90%
“…These results correspond to the previous time series ( Figure 2 b) and additionally suggest the requirement of further protein processing time for higher order oligomer assembly. It should be noted that the absence of microsomes reduced the protein yield, consistent with other studies [ 23 ] and thus causes overall weaker protein bands in the autoradiogram.…”
Section: Resultssupporting
confidence: 90%
“…3 C ). This nitrate-independent increase in luminescence upon addition of POPE may suggest that negative lipid curvature stabilizes the “on” conformation of NarX ( 44 ). The high induction of luciferase expression in POPE and POPG membranes is unsurprising as PE and PG make up the majority of lipid headgroups in E. coli membranes ( 46 ).…”
Section: Resultsmentioning
confidence: 98%
“…S5 ). Further, improper membrane protein folding has been found to increase aggregation and truncation products ( 41 , 44 ), and likely inhibits efficient expression of all protein components in the system. As a result of this relationship, we only considered NarX expression in our future analysis of the effect of membrane composition on NarX-L performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this peptide is unnecessary in our cell-free system that lacks a signal recognition particle and we hypothesized that the presence of the hydrophobic peptide in the nascent peptide chain might hinder the cotranslational integration of the membrane protein into liposome membranes. Further, we have previously found that sequence alterations in the nascent chain of a cell-free expressed membrane protein can have a profound impact on cell-free membrane protein expression (56). Specifically, we identified that alterations in protein sequence that inhibit protein-lipid interactions lead to membrane proteins that cannot successfully move off the ribosome and insert into membranes.…”
Section: Alterations In the Nascent Peptide Sequence Of Nipah Transme...mentioning
confidence: 99%